Analisis Aspek Keberlanjutan Lingkungan Berbasis Konservasi Warisan Alam dan Pengelolaan Sumber Daya pada Objek Wisata Pantai Penyu Nagari Ampiang Parak Kabupaten Pesisir Selatan - Ayu Suryani; Adil Mubarak (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
This research purposes to analyze environmental sustainability aspects based on natural heritage conservation and resource management at turtle beach tourism objects in Nagari Ampiang Parak, South Coastal District, researchers conducted research using qualitative methods with purposive sampling techniques, the techniques for data collection through observation, interviews and documentation. The validity test of the data using analysis by source triangulation, namely reduction for data, data presentation, make conclusions. The turtle beach destination is said to be environmentally sustainable in terms of natural heritage conservation and resource management. The results showed that natural heritage conservation management was not optimal, information media such as sites did not exist, resource management was not optimal because destinations did not yet have renewable energy, did not have guidelines for monitoring reduced water use and did not have data and reports on water quality.